2022
DOI: 10.1002/jsfa.12282
|View full text |Cite
|
Sign up to set email alerts
|

Transforming agrifood systems in a win–win for health and environment: evidence from organic rice–duck coculture

Abstract: BACKGROUND Rice–duck coculture is an ecological agricultural mode; however, the nutritional and environmental benefits of transforming from conventional rice monoculture to rice–duck coculture are unknown. Based on survey data and the life‐cycle assessment approach, this study conducted a carbon footprint evaluation of conventional rice monoculture (CR), organic rice monoculture (OR), and organic rice–duck coculture (ORD) using different functional units. RESULTS The carbon footprint per hectare of ORD (7842 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Simultaneously, its high carbon emissions and excessive pollution exert significant strain on the environment, which is not beneficial to sustainable agriculture development (Poulton et al, 2016;Liang et al, 2021;Gangopadhyay et al, 2022;Wu et al, 2022). Current academic research on LCRF technology focuses primarily on enhancing soil organic carbon accumulation (Xia et al, 2020;Wei et al, 2021;Tang et al, 2022;Zhang et al, 2022b), enhancing agricultural material utilization efficiency (Memon et al, 2018;Yadav et al, 2020;Zhang et al, 2020aZhang et al, , 2020b, and promoting carbon biocycling (Dai et al, 2022;Sultana et al, 2022;Gao et al, 2023). Based on a theoretical study of LCRF technology, this research lists the seven typical categories of LCRF behaviors based on regional rice farming features and empirical evidence.…”
Section: Theory and Technology Of Lcrfmentioning
confidence: 99%
“…Simultaneously, its high carbon emissions and excessive pollution exert significant strain on the environment, which is not beneficial to sustainable agriculture development (Poulton et al, 2016;Liang et al, 2021;Gangopadhyay et al, 2022;Wu et al, 2022). Current academic research on LCRF technology focuses primarily on enhancing soil organic carbon accumulation (Xia et al, 2020;Wei et al, 2021;Tang et al, 2022;Zhang et al, 2022b), enhancing agricultural material utilization efficiency (Memon et al, 2018;Yadav et al, 2020;Zhang et al, 2020aZhang et al, , 2020b, and promoting carbon biocycling (Dai et al, 2022;Sultana et al, 2022;Gao et al, 2023). Based on a theoretical study of LCRF technology, this research lists the seven typical categories of LCRF behaviors based on regional rice farming features and empirical evidence.…”
Section: Theory and Technology Of Lcrfmentioning
confidence: 99%
“…[7][8][9] Many researchers have done a lot of research on greenhouse gas emissions, soil fertility effect, rice growth characteristics, and ecological and economic benefits in RD farming. 4,[10][11][12][13][14][15] Numerous studies have demonstrated that RD farming can significantly reduce methane emissions from paddy fields compared with conventional rice farming. 7,12,16,17 This may be because activities of ducks increase the concentration of dissolved oxygen in the water body and, thus, methane produced in the soil can be oxidized more quickly, 11,18 helping to slow global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have done a lot of research on greenhouse gas emissions, soil fertility effect, rice growth characteristics, and ecological and economic benefits in RD farming 4,10‐15 . Numerous studies have demonstrated that RD farming can significantly reduce methane emissions from paddy fields compared with conventional rice farming 7,12,16,17 .…”
Section: Introductionmentioning
confidence: 99%